Assessing and propagating workers safety and health in flood disaster: an exploratory study in the Perlis, Northern Malaysia - Faridah, Wahab; Azuddin, Bahari, Lt Kol (B); Tunku Salha, Tunku Ahmad (Universiti Malaysia Perlis, 2009)
Organized by Centre for Communication Skills and Entrepreneurship UniMAP in collaboration with The Ministry of Higher Education Malaysia, 5th - 6th December 2008 at Putra Palace Hotel, Perlis.